SAT0660 PROPOSAL OF CORE OUTCOME DOMAINS IN MIXED CRYOGLOBULINEMIC VASCULITIS. (June 2019) - Guerrini, Giulio; Scirè, Carlo Alberto; Vultaggio, Licia; Giambalvo, Simone; Sebastiani, Marco; Vacchi, Caterina; Quartuccio, Luca; Pietrogrande, Maurizio; ,
Abstract : Background: Cryoglobulinaemic vasculitis is immune complex mediated vasculitis of medium and small-size vessels. This vasculitis involves mainly kidneys, peripheral nervous system, skin and joints. Currently, no standardized outcome measures are available for the evaluation of treatments in patients with cryoglobulinemic vasculitis. Objectives: To identify a core set of outcome measure (what to measure) for clinical studies for mixed cryoglobulinemic syndrome, following the OMERACT filter 2.0. [Ref] Methods: A search was made in Medline (via PubMed) and Embase using a standardized search [filter https://omeracthandbook.org/]. This review considered studies that included patients with Mixed (type 2 and 3) cryoglobulinemic syndrome, any type of outcome measures, articles in the English language and considered only SLR, RCT, cohort, case control and case series (>5 patients). Data were screened independently by three reviewers, recorded on a prespecified extraction form and summarized qualitatively. Considering core areas and core domain set was drafted. The results were presented and voted by a Consensus Committee including physicians with expertise in rheumatic, kidney and infectious diseases. Specific domains were separately voted and scored from 1 (strongly disagree) to 5 (strongly agree). Agreement was calculated as the percentage of agree/strongly agree. Consensus was reached in case of >70% of agreement. Results: In the review were included 88 studies of which 4 randomised clinical trial (3%, 144 patients), 3 systematic literature reviews (9%, 401 patients), 25 cohort studies (27%, 1284 patients), and 56 other observational studies (61%, 2871 patients). The most frequent domains were : bio-humoral activity markers (e.g. cryocrit, rheumatoid factor, complementemia), viral infection and liver function, reversible and non reversible manifestation of skin, peripheral nerve, kidney, joint. Only a few studies included as life impact area, survival and safety. No studies analyzed included economical impact. Drafted core domains within core areas and percent agreement from the Delphi survey are reported in Table I . Additional core domains included adverse events and viral infection, considered as contextual factor. Conclusion: This is the first study aimed at identifying the core outcome measures in cryoglobulinemic vasculitis. Further studies will be needed to evaluate appropriate instruments to measure these outcome domains to be applied in clinical trials and practice. References: [1] Boers M, Kirwan JR, Wells G, et al. Developing core outcome measurement sets for clinical trials: OMERACT filter 2.0. J Clin Epidemiol 2014;67:745–53. doi:10.1016/j.jclinepi.2013.11.013 Disclosure of Interests: None declared